2014
DOI: 10.1242/dev.102434
|View full text |Cite
|
Sign up to set email alerts
|

MIG-10 (lamellipodin) has netrin-independent functions and is a FOS-1A transcriptional target during anchor cell invasion in C. elegans

Abstract: To transmigrate basement membrane, cells must coordinate distinct signaling activities to breach and pass through this dense extracellular matrix barrier. Netrin expression and activity are strongly associated with invasion in developmental and pathological processes, but how netrin signaling is coordinated with other pathways during invasion is poorly understood. Using the model of anchor cell (AC) invasion in C. elegans, we have previously shown that the integrin receptor heterodimer INA-1/PAT-3 promotes net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 78 publications
0
34
0
Order By: Relevance
“…We also found that two additional MMPs expressed in the AC, zmp-3 and zmp-6 , were dependent on nhr-67 (Figure 4A and 4B). Finally, we examined the expression of actin regulators that promote invasive cellular behavior (Li et al, 2014; Wang et al, 2014). We found that AC expression of the actin regulators exc-6 (formin) and unc-34 (Ena/VASP) was dependent on NHR-67 activity, as RNAi depletion of nhr-67 resulted in reduced expression of exc-6 and unc-34 GFP transcriptional reporters (Figure 4A and 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that two additional MMPs expressed in the AC, zmp-3 and zmp-6 , were dependent on nhr-67 (Figure 4A and 4B). Finally, we examined the expression of actin regulators that promote invasive cellular behavior (Li et al, 2014; Wang et al, 2014). We found that AC expression of the actin regulators exc-6 (formin) and unc-34 (Ena/VASP) was dependent on NHR-67 activity, as RNAi depletion of nhr-67 resulted in reduced expression of exc-6 and unc-34 GFP transcriptional reporters (Figure 4A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…AC invasion is coordinated with the underlying vulval precursor cell P6.p divisions—the AC is specified at the P6.p one-cell stage, initiates invasion at the P6.p two-cell stage and completes invasion at the P6.p four-cell stage (Sherwood and Sternberg, 2003). Prior to invasion, a number of genes are upregulated in the AC that contribute to BM breaching, including the MMP zmp-1 , actin regulators, and the extracellular matrix component hemicentin (Morrissey et al, 2014; Sherwood et al, 2005; Wang et al, 2014; Ziel et al, 2009). Further, similar to metastatic cancer cells, the AC forms invadopodia that breach the BM (Hagedorn et al, 2014; Hagedorn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…et al 2013; Ghosh and Sternberg 2014;Wang et al 2014b). The contactin RIG-6 also functions cell autonomously in the canal, potentially as part of the UNC-53 pathway (Katidou et al 2013).…”
Section: Cytoskeletal Organization In the Growing Canalsmentioning
confidence: 99%
“…During AC invasion, the c-fos transcription factor ortholog fos-1 promotes expression the zinc metalloprotease zmp-1, the protocadherin cdh-3, the zinc finger protein egl-43, the hemicentin extracellular matrix protein gene him-4, and lamillopodin/mig-10; the activities of these genes induce the AC to form ventrally directed protrusions that breach the basement membrane ( Fig. 6A; Sherwood et al, 2005;Hwang et al 2007;Wang et al, 2014). RNAi against the AC invasion genes resulted in defects in utse development (Table 2E; Fig.…”
Section: Ac Invasion Genes Act During L4 To Affect Utse Developmentmentioning
confidence: 99%
“…Each of these genes are expressed within the AC during invasion (Sherwood et al, 2005;Hwang et al 2007;Wang et al, 2014). Since the AC nucleus is necessary for utse development, we asked if these genes were transcriptionally active throughout L4 and were present in the utse.…”
Section: Ac Invasion Genes Act During L4 To Affect Utse Developmentmentioning
confidence: 99%